Survival outcomes and contributing factors in oral squamous cell carcinoma patients in Khuzestan province, southwest of Iran - Karimi, Babak; Ghoreyshvandi, Arian; Cheraghi, Maria (Frontiers in Oncology, 2024)
BackgroundOral squamous cell carcinoma (OSCC) is the most frequent oral cancer worldwide. Despite advances in OSCC treatment, the mortality rate has not decreased in recent years. Therefore, the aim of this investigation was to assess the survival rate as a factor reflecting the quality aspects of care and background parameters that influence survival in patients with OSCC.MethodsThis is a retrospective analysis of 165 patients with OSCC who were registered in the Khuzestan cancer registry system in 2014 to 2018. The data were collected in two parts: demographic information and survival information. Demographic and background variables include age, gender, marital status, ethnicity, employment status, insurance status, and educational status. Survival information was also collected through phone calls to patients or their families. The survival rate of the patients was analyzed using the log-rank test and the influencing factors were analyzed with the Cox regression test.ResultsIn this study, 165 patients, 43 women (26.1%) and 122 men (73.9%), with OSCC were included. The follow-up period of the patients was 5 years (2014–2019), during which 74 patients died. One, three, and five-year survival rates were 93.34%, 71.51%, and 44.84%, respectively. The results showed that age (χ2 = 4.410, p < 0.05) and employee status (χ2 = 10.205, p < 0.05) were associated with survival rate in OSCC patients based on the log-rank test results, while Cox regression analysis, after including all variables in the model and adjusting them, showed that all variables were not associated with survival rate (p > 0.05).ConclusionSince all background factors were not associated with survival rate, efforts should continue to identify effective factors and investigate the relationship between survival and pathological factors such as recurrence status, distant metastasis, type of treatment, and involved organs.